The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1055665620959528
|View full text |Cite
|
Sign up to set email alerts
|

Is Risk of Secondary Surgery for Oronasal Fistula Following Primary Cleft Palate Repair Associated With Hospital Case Volume and Cost-to-Charge Ratio?

Abstract: Objective: This study assesses the association between risk of secondary surgery for oronasal fistula following primary cleft palate repair and 2 hospital characteristics—cost-to-charge ratio (RCC) and case volume of cleft palate repair. Design: Retrospective cohort study. Setting: This study utilized the Pediatric Health Information System (PHIS) database, which consists of clinical and resource-utilization data from >49 hospitals in the United States. Patients and Participants: Patients undergoing primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“… 1 These children require multidisciplinary care and reconstructive procedures throughout childhood and adolescence to support otolaryngologic improvement, speech and dental development alongside psychosocial well-being to mitigate negative impacts and barriers to social integration, given the functional and visible nature of the condition. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“… 1 These children require multidisciplinary care and reconstructive procedures throughout childhood and adolescence to support otolaryngologic improvement, speech and dental development alongside psychosocial well-being to mitigate negative impacts and barriers to social integration, given the functional and visible nature of the condition. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…However, other authors have suggested the use of secondary alveolar bone grafts for the purpose of better osteomucosal alveolar morphology. 710 This systematic review and meta-analysis was conducted to evaluate the long-term results of NAM and gingivoperiosteoplasty in patients with cleft lip/palate.…”
mentioning
confidence: 99%
“…However, other authors have suggested the use of secondary alveolar bone grafts for the purpose of better osteomucosal alveolar morphology. [7][8][9][10] This systematic review and meta-…”
mentioning
confidence: 99%